The Relationship between Physical Activity, Fitness and Educational Achievement of Rural South African Children: 南非鄉鎮兒童身體活動、體適能與學業成就的關係 - THEMANE, M. J.; KOPPES, L. L. J.; KEMPER, H. C. G.; MONYEKI, K. D.; TWISK, J. W. R. (Asian Journal of Physical Education & Recreation, 2006)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this study was to investigate the relationships of physical activity and physical fitness with educational achievement in rural South African school children aged 7 to 14 years (n= 212). All boys and girls underwent the following physical fitness tests: standing long jump, bent arm hang, sit ups, 10 x 5m shuttle run, 50 meter run, 1,600 meter run, flamingo balance, sit and reach, and plate tapping. All tests were performed in accordance with the European Tests of Physical Fitness (EUROFIT) and American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) protocols. A questionnaire was used to gather physical activity information concerning indoor and outdoor household activities, games and sports performed during the week days and weekend days. Educational achievement was assessed by means of the Educational Achievement Tests in Mathematics and English designed by South African Human Sciences Research Council. In contrast to what has been found in developed countries, the results of the present study did not show strong evidence for the hypothesis that physical activity and physical fitness are positively associated with educational achievement. Explanations for this finding may be that: first, the children in this population are confronted by a number of educational problems that may have confounded the relationship. Second, because all these children have high levels of physical activity it may be difficult to measure its influence on educational achievement, and third, the cross-sectional nature of this study. 本文旨在探討南非鄉鎮地區小學生身體活動量與學業的關係，以問卷方式進行調查，訪問了212名學童，並評估他們的體適能狀況，結果未能顯示出兩者呈現關係，這現象可能受到文化及敎育等因素影響所致，結果呈現兩種動作類，顯示對於下肢的偏向是取決於動作的。作者提出看法，認為各個不同孩童的互動、動作和環境的轉換都對下肢偏向起著影響。